2016
DOI: 10.1128/aac.01024-16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of β-Lactam-plus-Macrolide Combination Therapy in a Mouse Model of Lethal Pneumococcal Pneumonia

Abstract: b Community-acquired pneumonia is a common disease with considerable morbidity and mortality, for which Streptococcus pneumoniae is accepted as a leading cause. Although ␤-lactam-plus-macrolide combination therapy for this disease is recommended in several guidelines, the clinical efficacy of this strategy against pneumococcal pneumonia remains controversial. In this study, we examined the effects of ␤-lactam-plus-macrolide combination therapy on lethal mouse pneumococcal pneumonia and explored the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
3
20
0
1
Order By: Relevance
“…Azithromycin treatment also led to a significant suppression of lung MPO activity, suggesting that azithromycin inhibited the neutrophil infiltration into the lung parenchyma and alveolar spaces. Finding of our study is in agreement with earlier report where azithromycin had demonstrated beneficial effect in combination with ceftriaxone in mouse model of lethal pneumococcal pneumonia due to its immunomodulatory activity (28). In the present study, we have demonstrated immunomodulatory activity of azithromycin in both LPS and CLP sepsis model.…”
Section: Discussionsupporting
confidence: 93%
“…Azithromycin treatment also led to a significant suppression of lung MPO activity, suggesting that azithromycin inhibited the neutrophil infiltration into the lung parenchyma and alveolar spaces. Finding of our study is in agreement with earlier report where azithromycin had demonstrated beneficial effect in combination with ceftriaxone in mouse model of lethal pneumococcal pneumonia due to its immunomodulatory activity (28). In the present study, we have demonstrated immunomodulatory activity of azithromycin in both LPS and CLP sepsis model.…”
Section: Discussionsupporting
confidence: 93%
“…As azithromycin lacks antibacterial activity against the enteric bacteria which lead to mortality in mice, the LPS-induced sepsis model was used to identify the immunomodulatory dose of azithromycin that was later employed in the CLP-induced sepsis model. Treatment with an azithromycin dose of 100 mg/kg, which led to 75% survival of mice in the LPS sepsis model, was chosen as the immunomodulatory dose and is in the therapeutic range of azithromycin (19). As expected, the same dose did not provide equivalent protection in the CLPinduced sepsis model, suggesting its inability to stop the progression of infection.…”
Section: Discussionmentioning
confidence: 89%
“…133,134 This contention is supported by observations that administration of a betalactam/macrolide combination, which shows no synergistic activity against the pneumococcus in vitro, 135 demonstrates significant survival benefits relative to those of the individual agents in a murine model of lethal pneumococcal (macrolidesusceptible) pneumonia. 136 When compared with the individual agents, the beneficial effects of the ceftriaxone/azithromycin regimen used in this study were not associated with differences in lung bacterial loads at day 3 post-initiation of infection, but rather with immune modulation and anti-inflammatory activity characterised by decreased neutrophil influx. 136 The aforementioned studies also highlight the difficulty in distinguishing the anti-inflammatory activity of macrolides resulting from inhibition of synthesis of Ply and other pro-inflammatory pneumococcal virulence factors due to primary antimicrobial activity, from the secondary, host-targeted mechanisms described below.…”
Section: Macrolides and The Pneumococcusmentioning
confidence: 68%
“…136 When compared with the individual agents, the beneficial effects of the ceftriaxone/azithromycin regimen used in this study were not associated with differences in lung bacterial loads at day 3 post-initiation of infection, but rather with immune modulation and anti-inflammatory activity characterised by decreased neutrophil influx. 136 The aforementioned studies also highlight the difficulty in distinguishing the anti-inflammatory activity of macrolides resulting from inhibition of synthesis of Ply and other pro-inflammatory pneumococcal virulence factors due to primary antimicrobial activity, from the secondary, host-targeted mechanisms described below. Until the exact mechanisms underpinning the apparent benefit of betalactam/macrolide combination therapy of severe pneumococcal disease are unequivocally established, widespread acceptance of this strategy in the face of increasing levels of macrolide resistance is likely to remain contentious.…”
Section: Macrolides and The Pneumococcusmentioning
confidence: 68%